(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
The possibility of plantain (Plantago major L.) as traditional medicine that could be harvest by local people had been studied. The aims of the research were to know abundance and distribution of P. major, a medicinal plant, in southern slope of Mount Lawu. The research had done by using square method with transect along mountain tracking line from Cemoro Sewu base camp (Â± 1900 m asl) to Argo Dumilah peak (3265 m asl). The data was collected on 13 stations based on altitude, namely 1900-2000, 2000-2100, 2100-2200, 2200-2300, 2300- 2400, 2400-2500, 2500-2600, 2600-2700, 2700-2800, 2800-2900, 2900-3000, 3000-3100, and 3100-3200 m asl, each of them had 8 replication. The research result indicated that P. major had been found at 2200 m asl, and it would higher population at the higher altitude. The plant had clumped distribution pattern. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: Plantago major L., abundance, distribution, Mount Lawu.